The Role and Actions of the Intellectuals in the Awareness of National Identity in Uzbekistan in the Second Half of the 1980s - Juraev Utkir Ortikboyevich (Researchparks Publishing, 2021)
The article analyses the processes, the state and the problems of material and spiritual life in Uzbekistan in the second half of the 1980s, as well as the issues raised by intellectuals on the way to realising their national identity.